EVALUASI EFEKTIVITAS PENGENDALIAN INTERN ATAS SISTEM PENGGAJIAN DAN PENGUPAHAN (Studi Kasus Pada PT. Karyamitra Budisentosa Pandaan-Pasuruan) - Novia Damayanti (Jurnal Administrasi Bisnis, 2015)
Each company is required to compete and capable of conducting business activities optimally in order to try harder to develop and maintain business .To reach the goal the company must be capable of choosing and managing human resources properly and professionals .In the management of human resources the important thing  is to the application of the policy of compensation in a proper and right through salaries and wages .This research aims to understand whether effective internal control elements which is in a system of accounting  payroll  and remuneration on  PT.  Karyamitra  Budisentosa Pandaan-Pasuruan. An analysis of a case study descriptive used in this research . From the research can be known that there the separation of payroll functions salary list with the functioning of accounting, the function of timekeeper EDP (Electric Data Processing) with the functioning of the operation and the existence of an audit surprised periodically that shows that the application of payroll and wage system made effective enough to support the internal control.Suggestions can be delivered for the company on the payroll and wage system is among others , affirmation to job description employees especially in the HRD & GA , and additional forms / documents to the payroll and wage system manually, Money Salary Calculation Control Card ( KKPG ) .Keyword: Professional , Compensation , Effective , Surprised , An audit